The mechanism of high mobility group box-1 in the proliferation and macrophage polarization in esophageal squamous cell carcinoma cells - Liling Luo; Chao Jiang; Songxi Xie (European Journal of Medical Research)
Abstract Background Previous studies showed that high mobility group box-1 (HMGB1) facilitates the initiation and progression of esophageal squamous cell carcinoma (ESCC), and the current research investigated the detailed mechanisms implicated. Methods The impact of HMGB1 and IGFBP3 levels on the survival of ESCC was examined by plotting Kaplan–Meier (KM) curves based on the data collected from The Cancer Genome Atlas (TCGA). Quantitative real-time PCR (qRT-PCR) was performed to detect the expressions of HMGB1 in both human esophageal epithelial cells (HEEC) and ESCC cells. After cell transfection, the proliferation of ESCC cells was measured, and the cell metastasis was determined based on the levels of cadherins (CDHs) and Vimentin (VIM). Macrophage polarization was determined by calculating the mean fluorescence intensity (MFI) of CD206 and CD86. In addition, co-immunoprecipitation and immunoblotting were applied to evaluate the interaction between insulin-like growth factor binding protein 3 (IGFBP3)/DNA-dependent protein kinase catalytic subunit (DNA–PKcs) and HMGB1. Results A high level of HMGB1 was predictive of an unfavorable prognosis of ESCC (p < 0.05). HMGB1 showed a higher expression in ESCC cells (p < 0.05), while knockdown of HMGB1 inhibited ESCC cell proliferation, downregulated the levels of CDH2 and VIM and upregulated the level of CDH1 (p < 0.05). In contrast, overexpressed HMGB1 showed the opposite effects (p < 0.05), suggesting the role of HMGB1 in the epithelial–mesenchymal transition (EMT) of ESCC. After the knockout of HMGB1, the MFI of CD86 was increased but that of CD206 was reduced, indicating the polarization towards M1 macrophages (p < 0.05). However, the results were reversed when HMGB1 was overexpressed (p < 0.05). Meanwhile, HMGB1 could interact with the IGFBP3/DNA–PKcs complex (p < 0.05). Low-expressed IGFBP3 was predictive of an unfavorable prognosis of ESCC, and IGFBP3 silencing promoted the proliferation of ESCC cells (p < 0.05). Besides, HMGB1 and IGFBP3 could act antagonistically in influencing the proliferation of ESCC cells and macrophage polarization. Conclusions Through in vitro experiments, this study found that HMGB1 was linked to the proliferation and polarization of macrophages in ESCC, providing novel evidence for the role of HMGB1 in ESCC development.